Synthesis and characterisation of hydroxyapatite from fringescale sardinella for biomedical applications - Hussin, Mohamed Saiful Firdaus; Idris, Maizlinda Izwana; Abdullah, Hasan Zuhudi; Mohamed Sultan, Al Amin (2022)
Hydroxyapatite (HAp) from fish by-product exhibits good biocompatibility and bioactivity on implants. The aim of the study is to investigate the elemental composition, crystalline phases, and functional groups of HAp synthesised from fringescale sardinella fish bones by heat decomposition method at temperature of 600, 900, and 1200 °C. The synthesised powders were characterized using fourier transform infrared spectroscopy (FTIR), X-ray diffraction (XRD), and energy dispersive spectroscopy (EDS). After calcination of the raw fish bone to 600, 900, and 1200 °C, the FTIR data showed the existence of phosphate and hydroxyl peaks in the calcined fish bones. At 900 and 1200°C, the XRD data observed shows well-defined peaks of HAp pattern. The elemental composition evaluated by EDS provides information on the calcium to phosphate formation into apatite with a Ca/P ratio of 2.80, 0.98, 1.64 and 1.79 atomic % for raw fish bones and calcined samples, respectively. It can be concluded that the fringescale sardinella fish bones show promising findings particularly on the synthesisation of HAp for biomedical applications